2012
DOI: 10.3346/jkms.2012.27.1.27
|View full text |Cite
|
Sign up to set email alerts
|

LPS-Induced Migration of Peritoneal B-1 Cells is Associated with Upregulation of CXCR4 and Increased Migratory Sensitivity to CXCL12

Abstract: B-1 cells, which constitute a predominant lymphocyte subset in serosal cavities and produce most of natural antibodies, are subdivided into the CD5+ B-1a and CD5- B-1b cell subpopulations, but the differential roles of B-1a and B-1b cells are not well understood. We report that B-1a cells preferentially migrate out of the peritoneal cavity and upregulate the expression of CXCR4 with heightened sensitivity to CXCL12 and CXCL13 upon LPS treatment compared to B-1b and B-2 cells. Whereas B-1a cells were slightly m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
23
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 30 publications
3
23
0
Order By: Relevance
“…A recent study has also reported a similar observation, noting that B1-a B cells rapidly disappear from the peritoneal cavity following i.p. LPS injection and attributed this to chemokine-mediated migration toward CXCL12 and CXCL13 gradients - although only CXCR4 expression is increased on B1-a B cells while CXCR5 expression remains constant [20]. We observed a similar reduction in B1-a B cell frequency in PECs (Fig.…”
Section: Resultssupporting
confidence: 59%
“…A recent study has also reported a similar observation, noting that B1-a B cells rapidly disappear from the peritoneal cavity following i.p. LPS injection and attributed this to chemokine-mediated migration toward CXCL12 and CXCL13 gradients - although only CXCR4 expression is increased on B1-a B cells while CXCR5 expression remains constant [20]. We observed a similar reduction in B1-a B cell frequency in PECs (Fig.…”
Section: Resultssupporting
confidence: 59%
“…For example, infection or inflammation-driven production of IL-33 triggers the production of IL-5 by ILC2 cells, which in turn promotes the differentiation of local B1 cells in the FALCs and MS [15]. Peritoneal administration of LPS also promotes the migration of peritoneal B1 cells to the MS [50, 51, 61], where they differentiate into IgM-secreting and IgA-secreting cells, some of which colonize the intestine [67, 68], possibly by CXCR4-dependent mechanisms [69]. The omentum also supports the formation and local maintenance of IgM + memory B cells and CD11c + IgM plasmablasts in response to peritoneal infection [47].…”
Section: Immune Responses In the Omentummentioning
confidence: 99%
“…CXCL13 is required for B-1 cell migration to and from the peritoneal cavity 21, 22 , whereas up-regulation of CXCR4 and corresponding CXCL12 responsiveness following LPS stimulation induced the efflux of B-1 cells from the peritoneal cavity 23 . Others showed a MyD88-dependent decrease in peritoneal B-1 cell frequencies in response to the introduction of intestinal bacteria or LPS into that site and an increase of B-1 cells in omentum and mesenteric lymphoid tissues.…”
mentioning
confidence: 99%